2023
DOI: 10.3390/antiox12030660
|View full text |Cite
|
Sign up to set email alerts
|

Application of Agri-Food By-Products in Cheesemaking

Abstract: Agri-food companies produce large quantities of plant by-products that in many instances contain functional bioactive compounds. This review summarizes the main applications of agro-industrial by-products in cheesemaking, considering their bioactivities and functional properties. Polyphenol-rich by-products increase antioxidant and antimicrobial activity in cheeses, positively impacting their shelf life. Contrasting results have been obtained regarding the color and sensory properties of enriched cheeses depen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 78 publications
0
5
0
Order By: Relevance
“…Fruit and vegetable industry produces a significant quantity of waste and byproducts, representing 10% to 35% of the gross mass (Majerska et al, 2019). The potential of byproducts refers to the presence of bioactive compounds to be added in food formulation (Difonzo et al, 2023). Cucumber peel is a good source of dietary fiber and phytochemicals compounds such as polyphenols (8.51 mg/g), glycosides (32.23 mg/g), terpenoids (26.27 mg/g), and steroids (11.69 mg/g).…”
Section: Agri-food Byproductsmentioning
confidence: 99%
See 1 more Smart Citation
“…Fruit and vegetable industry produces a significant quantity of waste and byproducts, representing 10% to 35% of the gross mass (Majerska et al, 2019). The potential of byproducts refers to the presence of bioactive compounds to be added in food formulation (Difonzo et al, 2023). Cucumber peel is a good source of dietary fiber and phytochemicals compounds such as polyphenols (8.51 mg/g), glycosides (32.23 mg/g), terpenoids (26.27 mg/g), and steroids (11.69 mg/g).…”
Section: Agri-food Byproductsmentioning
confidence: 99%
“…Fruit and vegetable industry produces a significant quantity of waste and byproducts, representing 10% to 35% of the gross mass (Majerska et al., 2019). The potential of byproducts refers to the presence of bioactive compounds to be added in food formulation (Difonzo et al., 2023).…”
Section: Plant‐derived Extracts and Essential Oilsmentioning
confidence: 99%
“…In fact, different studies reported that these matrices are a food source of antioxidant compounds, such as polyphenols [42][43][44][45][46][47][48]. Table 4 shows the antioxidant activity and the total phenol content of the extracts from VS and GS; the extracts obtained with an aqueous solution showed the highest ABTS and DPPH values and total polyphenols content (65.67 and 250.14 µmol TE/g, and 58.03 mg GAE/g respectively).…”
Section: Phenolic Compounds Characterizationmentioning
confidence: 99%
“…Mango peel which is agood sources of numerous phenolic compounds and phytochemicals; is considered one ofantioxidant agents. It contains carotenoids, enzymes, minerals, pectin, lipids, proteins and dietary fibers beside its content of vitamins E and C (Difonzo et al, 2023). Due to its content of dietary fibers and pectin, mango peels can improvethe texture and physical properties of food (owing to the water and oil holding capacities) and might be used as prebiotic for enhancing the growth of probiotic bacteria (Hussein et al, 2020;Thambi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…Due to its content of dietary fibers and pectin, mango peels can improvethe texture and physical properties of food (owing to the water and oil holding capacities) and might be used as prebiotic for enhancing the growth of probiotic bacteria (Hussein et al, 2020;Thambi et al, 2016). It was reported that mango peels have antioxidant activity and antimicrobial action against numerous pathogenic bacteria such as E.coli, Staphylococcus, Salmonella and Listeria monocytogenes (Cheng et al, 2022;Difonzo et al, 2023).…”
Section: Introductionmentioning
confidence: 99%